Creative Destruction and Productive Preemption - Pehr-Johan Norbäck; Lars Persson; Roger Svensson (Research Institute of Industrial Economics (IFN), 2009)
We develop a theory of commercialization mode (entry or sale) of entrepreneurial inventions into oligopoly, and show that an invention of higher quality is more likely to be sold (or licensed) to an incumbent due to strategic product market effects on the sales price. Moreover, preemptive acquisitions by incumbents are shown to stimulate the process of creative destruction by increasing the entrepreneurial effort allocated to high-quality invention projects. Using detailed data on patents granted to small firms and individuals, we find evidence that high-quality inventions are often sold, and that they are sold under bidding competition.
Keywords: G24; L10; L20; M13; O30; 330; Acquisitions; Entrepreneurship; Innovation; Start-ups; Patent; Ownership; Quality; Innovation; Patent; Unternehmensgründung; Kommerzialisierung; Schumpeterismus; Übernahme; Probit-Modell; Theorie